2020
DOI: 10.3390/ijerph17051718
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy as Communicative Action—A Qualitative Study among Persons at Risk in the Context of Predictive and Preventive Medicine

Abstract: Predictive and preventive medicine play an increasingly important role in public debates on health, providing cutting-edge technologies with the potential to measure and predict individual risks of getting ill. This leads to an ever-expanding definitional space between being “healthy” and being “ill”, challenging the individual’s everyday life, attitudes and perceptions towards the self and the process of health-related decision-making. “How do the condition of ‘being at risk’ and individual health literacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 42 publications
(58 reference statements)
3
28
0
3
Order By: Relevance
“…Rather, health literacy in transcultural treatment settings appears to be an interplay of several external and internal factors that influence information delivery on the one hand and information processing on the other. This finding is in line with other qualitative studies that emphasize the social-relational character of health literacy, discussing it as social practice [44] and communicative action [45]. For the purpose of this study, the integrated model of health literacy [3] provided helpful guidance.…”
Section: Discussionsupporting
confidence: 86%
“…Rather, health literacy in transcultural treatment settings appears to be an interplay of several external and internal factors that influence information delivery on the one hand and information processing on the other. This finding is in line with other qualitative studies that emphasize the social-relational character of health literacy, discussing it as social practice [44] and communicative action [45]. For the purpose of this study, the integrated model of health literacy [3] provided helpful guidance.…”
Section: Discussionsupporting
confidence: 86%
“…The theme of power and solidarity recorded that the power of doctorsis declining. In conformity with the findings of a study by Harzheim et al, the researchers found that patients are becoming autonomous and powerful because healthcare has become a commodity 16 . The doctors have assumed the role of producers while the patients are consumers.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, several previous studies found aspects that are related to the need for control that we found. This includes the perceived importance of sharing responsibilities with health professionals [22], the need to be assertive in interactions with doctors [23], and the role of motivation in facilitating the development of HL [18,21]. With regard to experienced barriers in using the health care system, other studies found some similar ones, including time constraints in doctor consultations [22,23] and poor communication with health professionals [18,20,26].…”
Section: Discussionmentioning
confidence: 96%
“…This includes work by Edwards et al [18], who conducted a longitudinal qualitative study on how patients with a long-term health condition became more health-literate over time in the UK, and by Van Onna et al [19], who studied HL in patients with gout in the Netherlands. Furthermore, there are studies on HL of diabetic Chinese immigrants in the US [20] and on HL of persons at risk of becoming chronically ill in Germany [21].…”
Section: Introductionmentioning
confidence: 99%